Study of Green Human Resource Management Implementation on Employees of PT. Telkom Indonesia Tbk - Meita Selina Istiqomah; Indi Djastuti (Eduvest - Journal of Universal Studies, 2022)
The occurrence of global warming and climate change has caused a commotion around the world, applying the principle of going green is not something that only has to be done in the personal environment but must be done anywhere including in the work environment. Currently, the company provides many opportunities for employees to implement go green behavior. From customizing the office lighting system to the type of office equipment they will choose and use, at least there are many things they can do to make the office environment more environmentally friendly. The idea of introducing a go green initiative into the workplace can seem a little difficult at first. While it can be difficult trying to figure out where to start, there are actually many ways that companies can be more environmentally friendly in the office environment without major cost implications with long term benefits for both the company and employees. The application of environmentally friendly behavior in human resource management is also called Green Human Resources Management (GHRM). This study examines a state-owned enterprise (BUMN) engaged in the information and communication technology (ICT) service industry, namely PT Telkom Indonesia TBK. This research focuses on the types of GHRM practices implemented in the company environment, the factors that encourage companies to implement GHRM practices, employee understanding of these practices between generations such as baby boomers, gen x, and gen y, efforts and socialization of the company so that GHRM practices continue. The results found in this study that there have been several GHRM practices that have been carried out but for the understanding of the term GHRM it is not understood by the baby boomers generation. Employees in this generation are more familiar with the term go green.